Neuromodulation and Individuality - Maloney, Ryan T. (Frontiers in Behavioral Neuroscience, 2021)
Within populations, individuals show a variety of behavioral preferences, even in the absence of genetic or environmental variability. Neuromodulators affect these idiosyncratic preferences in a wide range of systems, however the mechanism(s) by which they do so is unclear. I review the evidence supporting three broad mechanisms by which changes in neuromodulators might affect variability in idiosyncratic behavioral variability: by being a source of variability directly upstream of behavior, by affecting the behavioral output of a circuit in a way that masks or accentuates underlying variability in that circuit, and by driving plasticity in circuits leading to either homeostatic convergence towards a given behavior or divergence from a developmental setpoint. I find evidence for each of these mechanisms and propose future directions to further understand the complex interplay between individual variability and neuromodulators.